Foxd3 suppresses interleukin‐10 expression in B cells. Issue 4 (12th January 2017) - Zhang, Yu; Wang, Zhiding; Xiao, He; Liu, Xiaoling; Zhu, Gaizhi; Yu, Dandan; Han, Gencheng; Chen, Guojiang; Hou, Chunmei; Ma, Ning; Shen, Beifen; Li, Yan; et al.
Summary: Interleukin‐10‐positive (IL‐10 + ) regulatory B (Breg) cells play an important role in restraining excessive inflammatory responses by secreting IL‐10. However, it is still unclear what key transcription factors determine Breg cell differentiation. Hence, we explore what transcription factor plays a key role in the expression of IL‐10, a pivotal cytokine in Breg cells. We used two types of web‐based prediction software to predict transcription factors binding the IL‐10 promoter and found that IL‐10 promoter had many binding sites for Foxd3. Chromatin immunoprecipitation PCR assay demonstrated that Foxd3 directly binds the predicted binding sites around the start codon upstream by −1400 bp. Further, we found that Foxd3 suppressed the activation of IL‐10 promoter by using an IL‐10 promoter report system. Finally, knocking out Foxd3 effectively promotes Breg cell production by up‐regulating IL‐10 expression. Conversely, up‐regulated Foxd3 expression was negatively associated with IL‐10 + Breg cells in lupus‐prone MRL/lpr mice. Hence, our data suggest that Foxd3 suppresses the production of IL‐10 + Breg cells by directly binding the IL‐10 promoter. This study demonstrates the mechanism for Breg cell production and its application to the treatment of autoimmune diseases by regulating Foxd3 expression. Abstract : Foxd3 directly binds the predicted binding sites of IL‐10 promoter; Foxd3 suppressed IL‐10 promoter activation; Knock down of Foxd3 effectively promotes IL‐10‐producing Breg cell production.